Estrogen maintains myometrial tumors in a lymphangioleiomyomatosis model. Issue 4 (April 2016) - Prizant, Hen; Taya, Manisha; Lerman, Irina; Light, Allison; Sen, Aritro; Mitra, Soumya; Foster, Thomas H; Hammes, Stephen R
Abstract: Lymphangioleiomyomatosis (LAM) is a rare disease in women. Patients with LAM develop metastatic smooth-muscle cell adenomas within the lungs, resulting in reduced pulmonary function. LAM cells contain mutations in tuberous sclerosis genes ( TSC1 or TSC2 ), leading to up-regulation of mTORC1 activity and elevated proliferation. The origin of LAM cells remains unknown; however, inactivation of Tsc2 gene in the mouse uterus resulted in myometrial tumors exhibiting LAM features, and approximately 50% of animals developed metastatic myometrial lung tumors. This suggests that LAM tumors might originate from the uterine myometrium, possibly explaining the overwhelming prevalence of LAM in female. Here, we demonstrate that mouse Tsc2 -null myometrial tumors exhibit nearly all the features of LAM, including mTORC1/S6K activation, as well as expression of melanocytic markers and matrix metalloproteinases (MMPs). Estrogen ablation reduces S6K signaling and results in Tsc2 -null myometrial tumor regression. Thus, even without TSC2, estradiol is required to maintain tumors and mTORC1/S6K signaling. Additionally, we find that MMP-2 and -9, as well as neutrophil elastase (NE), are overexpressed in Tsc2 -null myometrial tumors in an estrogen-dependent fashion. In vivo fluorescent imaging using MMP- or NE-sensitive optical biomarkers confirms that protease activity is specific to myometrial tumors. Similar to LAM cells, uterine Tsc2 -null myometrial cells also overexpress melanocytic markers in an estrogen-dependent fashion. Finally, we identify glycoprotein NMB (GPNMB) as a melanocytic marker up-regulated in Tsc2 -null mouse uteri and human LAM samples. Our data highlight the potential importance of estradiol in LAM cells, suggesting that anti-estrogen therapy may be a treatment modality. Furthermore, proteases and GPNMB might be useful LAM biomarkers.